Comparison Between Inertial Sensors and Motion Capture System to Quantify Flexion‐Extension Motion in the Back of a Horse. (June 2014) - Martin, P; Chateau, H; Pourcelot, P; Duray, L; Cheze, L
Abstract : Introduction: The development of miniaturized inertial sensor technology (IMU) opens new possibilities to assess equine back motion in real‐life situations. The consistency of IMU for measuring dorsoventral displacement of the back has been assessed but orientation has not. The aim of this study was to assess accuracy and consistency of miniaturized inertial sensors for quantification of flexion‐extension of the equine back, compared to motion capture (mocap) as a gold standard. Methods: One sound horse was trotted (3.5 m/s) and cantered (9 m/s) on a treadmill with synchronized mocap and IMU data collection. The amplitudes of two flexion‐extension angles were calculated between 3 IMUs (T12‐T16‐L2) and with a triad of markers linked to each IMU during 15 consecutive strides for two recordings at each gait. Consistency of sensor measurements was assessed using Lin correlation coefficient. Results: Thoracic and thoracolumbar angles showed respectively a Lin correlation coefficient of 0.96 (excellent) and 0.87 (good). The difference (mean ± SD) between IMU and mocap were, respectively for the thoracic and thoracolumbar angles, 0.57 ± 0.44 and 0.65 ± 0.47 degrees during trotting, and 0.83 ± 0.67 and 0.63 ± 0.44 degrees during canter. Conclusions: Angle values calculated with IMU data showed acceptable accuracy consistency for quantification of flexion‐extension movement in a horse's back. These results are encouraging for future development of the method in real‐life situations where mocap systems are unsuited for the quantification of back movements. Ethical Animal Research: None declared.Sources of funding: The authors thank the Institut Français du Cheval et de l′Equitation, the Association Nationale de la Recherche et de la Technologie and the Conseil Régional d′Aquitaine for financial support, the Pôle Hippolia for logistical support, and CIRALE for loaning the treadmill and the horse.Competing interests: none.